2022
DOI: 10.2147/ijgm.s349722
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Blood Urea Nitrogen to Albumin Ratio in Long-Term Mortality in Intensive Care Unit Patients with Acute Myocardial Infarction: A Propensity Score Matching Analysis

Abstract: Background Blood urea nitrogen to albumin ratio (BAR) has been implicated in predicting outcomes of various inflammatory-related diseases. However, the predictive value of BAR in long-term mortality in patients with acute myocardial infarction (AMI) has not yet been evaluated. Methods In this retrospective cohort study, the patients were recruited from the Medical Information Mart for Intensive Care III (MIMIC III) database and categorized into two groups by a cutoff va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…Recently, BAR has been used as a new biomarker to assess the prognosis of various diseases and is an important prognostic factor for death in several diseases, such as pulmonary embolism, 25 sepsis, 9 and lung cancer 26 . Moreover, numerous studies have identified BAR as an independent predictor for mortality risk of AMI 30,39 . In present study, we observed significantly higher BAR levels in patients with LVA.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, BAR has been used as a new biomarker to assess the prognosis of various diseases and is an important prognostic factor for death in several diseases, such as pulmonary embolism, 25 sepsis, 9 and lung cancer 26 . Moreover, numerous studies have identified BAR as an independent predictor for mortality risk of AMI 30,39 . In present study, we observed significantly higher BAR levels in patients with LVA.…”
Section: Discussionsupporting
confidence: 65%
“…15 In the retrospective study of Zhao et al in 1827 patients diagnosed with acute myocardial infarction in 2022; they concluded that BAR was calculated as 11.06 (7-18.59) (p<0.001) in the mortality group and 10.42 (7-16.71) in the fouryear mortality group, and that a higher BAR value could be used as an independent predictor for four-year mortality. 18 In a study by Lee et al in patients with lower GI bleeding in 2021, BUN ≥ 30 mg/dL and albumin ≤ 3.0 g/dL were associated with all-cause mortality. 19 In the study of Bae et al, the data of 596 geriatric patients with GI bleeding were analyzed and BAR and AIMS65 scores were compared.…”
Section: Discussionmentioning
confidence: 97%
“…In another study in which the prognostic value of the BAR was compared with the acute physiology score III, systemic inflammatory response syndrome and sequential organ failure assessment in patients with acute myocardial infarction, it was found that the AUC value of the BAR was higher compared with these scores. 38 In our study, the cut-off value for the BAR was determined as 4.…”
Section: Discussionmentioning
confidence: 98%